The Old Testament speaks a complete survey of Old Testament history and literature - Schultz, Samuel J. (San Fransisco, CA Harper, 2000)
Includes bibliographical references and indexes.
First edition published 1960.
Keywords: Bible. O.T. -- history of Biblical events; Bible. O.T. -- introductions